Intraventricular Fluid Injection as a Novel Treatment of Subdural Fluid Collection after VP Shunt Overdrainage: A Case Report - Budiwaluyo, Christian; Morota, Nobuhito; Yudhadi, Adhitya Rahadi; Yamamoto, Aya; Ihara, Satoshi; Tsuda, Kyoji (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Introduction: Subdural fluid collection is one of many complications of ventriculoperitoneal (VP) shunt. Variety of surgical procedures have been applied for the treatment of the post VP shunt subdural fluid collection, but the ideal surgical treatment remains controversial. Case Report: This is a case report of 14 years old boy who had a history of multiple VP shunt revisions for post hemorrhagic hydrocephalus with subdural fluid collections due to cerebrospinal fluid (CSF) overdrainage. Result: The author performed intraventricular fluid injection via shunt valve to expand the brain mantle and drain the subdural fluid through a small craniotomy. This is the first case report using the novel “fluid infusion” technique for the treatment of intractable subdural fluid collection after the VP shunt overdrainage. Conclusion: The technique can bring potentially great impact for the future treatment of symptomatic subdural fluid collection associated with CSF overdrainage after VP shunt.